Compositional Differences in the Habitat-Forming Bryozoan Communities of the Antarctic Shelf - Santagata, Scott; Ade, Veronica; Mahon, Andrew R.; Wisocki, Phillip A.; Halanych, Kenneth M. (Frontiers in Ecology and Evolution, 2018)
In some areas of the Antarctic shelf, bryozoans are abundant, acting as ecosystem engineers creating secondary structures with wide benthic coverage and harboring numerous other species. As the combined forces of global warming and ocean acidification threaten these habitats, we measured the composition of habitat-forming bryozoan communities using two techniques for imaging the sea floor, a YoYo-camera system and the AWI Ocean Floor Observation System (OFOS). YoYo-camera transects of the Bellingshausen, Amundsen, and Ross Seas were conducted during a research cruise on the R/V Nathaniel B. Palmer in 2013. OFOS transects included sites in the northern Palmer Archipelago where it borders the Scotia Sea and the Weddell Sea as part of the DynAMO project during the PS81 and PS96 cruises of R/V Polarstern in 2013 and 2015-16, respectively. Areas of bryozoan colonies were measured from the sea floor images using machine-learning algorithms available through the Trainable Weka Segmentation plugin developed for FIJI software. Habitat-forming bryozoan communities in the Palmer Archipelago and Ross Sea were largely composed of anascan flustrid species with finely mineralized skeletons, and to a lesser extent by other ascophoran lepraliomorph and umbonulomorph species having more robustly mineralized skeletons. Although habitat-forming bryozoan communities in the shallower (200 m) sites of the Weddell Sea also contained flustrid species, percent area and composition of flustrid bryozoans declined with increasing depth. Lepraliomorph and umbonulomorph bryozoan morphotypes were more abundant in the Weddell Sea, maintaining their relative percent area and increasing their percent composition between 200 - 400 m. Moreover, our analyses of species composition based on externally gathered datasets show similar trends among sites, depths, and degrees of colony mineralization to our seabed imaging study. Variation present in the bryozoan species compositions of the Amundsen and Bellingshausen Seas suggest that these areas potentially represent divergent bryozoan communities requiring further validation via remote imaging surveys. Overall, compositional differences among Antarctic habitat-forming bryozoan communities are likely influenced by the combined effects of seasonal ice scour and carbonate chemistry, which in an increasingly acidified and warming ocean may put the communities of the eastern Weddell Sea at greater risk.